Emphysematous gastritis after radical subtotal gastrectomy for advanced gastric cancer - Jou-Chien Liao (Formosan Journal of Surgery, 2018)
Emphysematous gastritis is a rare but severe disease characterized by air within the gastric wall. It is commonly caused by a bacterial infection and carries a remarkably high mortality rate (50%–60%). The most common predisposing factors include ingestion of corrosive substances, alcohol abuse, and recent abdominal surgery. Diagnosis of emphysematous gastritis is difficult and relies on computed tomography (CT) scan because of the nonspecific clinical presentation of abdominal pain with systemic toxicity. In this report, we present a case of a 78-year-old male with gastric adenocarcinoma who underwent laparoscopic radical subtotal gastrectomy. After the operation, he complained of severe abdominal pain and fever. Subsequently, the patient developed acute respiratory distress syndrome and septic shock. A CT scan performed on postoperative day 17 revealed extensive intramural gas in the stomach. The patient was diagnosed with emphysematous gastritis and received conservative treatment.